Wetland management proceedings of the international conference organized by the Institution of Civil Engineers and held in London on 2-3 June 1994 - Falconer, R. A.; Goodwin, P. (Thomas Telford, 1994)
Aims to summarize the components of successful wetland restoration programmes. This book provides all those involved in the management of wetlands, with an understanding of the physical, chemical and biological processes and the socio-economic aspects affecting wetlands, and how these processes are influenced by engineers, scientists and planners.